P10.02 Combined methods of a micropump system and a chronic cranial window allows tumor observation with multi photon laser scanning microscopy under continuous treatment. (9th September 2021) - Weil, S; Jung, E; Domínguez Azorín, D; Higgins, J; Reckless, J; Ramsden, N; Keller, P; Grainger, D; Wick, W; Winkler, F
Abstract: BACKGROUND: Glioblastomas are notoriously therapy resistant tumors. As opposed to other tumor entities, no major advances in therapeutic success have been made in the past decades. This has been calling for a deeper biological understanding of the tumor, its growth and resistance patterns. We have been using a xenograft glioma model, where human glioblastoma cells are implanted under chronic cranial windows and studied longitudinally over many weeks and months using multi photon laser scanning microscopy (MPLSM). To test the effect of (new) drugs, a stable and direct delivery system avoiding the blood-brain-barrier has come into our interest. MATERIAL AND METHODS: We implanted cranial windows and fluorescently labeled human glioblastoma stem-like cells into NMRI nude mice to follow up on the tumor development in our MPLSM model. After tumor establishment, an Alzet® micropump was implanted to directly deliver agents via a catheter system continuously over 28 days directly under the cranial window onto the brain surface. Using the MPLSM technique, the continuous delivery and infusion of drugs onto the brain and into the tumor was measured over many weeks in detail using MPLSM. RESULTS: The establishment of the combined methods allowed reliable concurrent drug delivery over 28 days bypassing the blood-brain-barrier. Individual regions and tumor cells could be measured and followed up before, and after the beginning of the treatment, as well as after the end of the pump activity. Fluorescently labelled drugs were detectable in the MPLSM and its distribution into the brain parenchyma could be quantified. After the end of the micropump activity, further MPLSM measurements offer the possibility to observe long term effects of the applied drug on the tumor. CONCLUSION: The combination of tumor observation in the MPSLM and concurrent continuous drug delivery is a feasible and reliable method for the investigation of (novel) anti-tumor agents, especially drugs that are not blood-brain-barrier penetrant. Morphological or even functional changes of individual tumor cells can be measured under and after treatment. These techniques can be used to test new drugs targeting the tumor, its tumor microtubes and tumor cells networks, and measure the effects longitudinally.